Water quality dynamics during extensive and intensive culture of the tiger shrimp, Penaeus monodon Fabricius - Baylon, Carlos C. (2003)
Water quality dynamics was monitored during the extensive and intensive culture of the tiger shrimp (Penaeus monodon Fabricius) in experimental ponds at the Brackishwater Aquaculture Station, Iloilo, Philippines. In the extensive culture method, the ponds were stocked with 2 postlarvae per m-2. The shrimps were provided with natural food and commercial feeds, and water management was through tidal exchange. In the intensive culture method, the ponds were stocked with 20 postlarvae per m-2. The shrimps were fed solely with commercial feeds, water exchange was facilitated with a pump, and pond aeration was by a paddle wheel. The shrimps were cultured for 156 o Dissolved oxygen (DO), pH, hydrogen sulfide (H2S), total ammonia nitrogen (TAN) and nitrite (NO2-N) were determined on a weekly basis and within 24-h cycles on wks 5 and 21. The weekly values for DO and pH fluctuated similarly in both the extensive (ECP) and intensive culture ponds (ICP). Weekly concentrations of H2S, TAN and NO2-N increased considerably toward the latter part of culture period in the intensive culture ponds, while corresponding increases were minimal in the extensive culture ponds. Over a 24-h monitoring period, DO and pH values peaked during the day and declined during the night in both culture systems. During the latter part of culture period, levels of H2S in the ICP were higher during the day than at night. A gradual buildup of TAN and NO2-N was observed during the night.
Keywords: Water quality; Shrimp culture